Mortality with brainstem seizures from focal 4‐aminopyridine–induced recurrent hippocampal seizures. (10th July 2017) - Salam, Muhammad Tariqus; Montandon, Gaspard; Genov, Roman; Devinsky, Orrin; Del Campo, Martin; Carlen, Peter L.
Summary: Objective: Sudden unexplained death in epilepsy is the leading cause of death in young adult epilepsy patients, typically occurring during the early postictal period, presumably resulting from brainstem and cardiorespiratory dysfunction. We hypothesized that ictal discharges in the brainstem disrupt the cardiorespiratory network, causing mortality. To study this hypothesis, we chose an animal model comprising focal unilateral hippocampal injection of 4‐aminopyridine (4‐AP), which produced focal recurrent hippocampal seizures with secondary generalization in awake, behaving rats. Methods: We studied ictal and interictal intracranial electrographic activity (iEEG) in 23 rats implanted with a custom electrode array into the hippocampus, the contralateral cortex, and brainstem. The hippocampal electrodes contained a cannula to administer the potassium channel blocker and convulsant (4‐AP). iEEG was recorded continuously before, during, and after seizures induced by 4‐AP infusion into the hippocampus. Results: The control group (n = 5) was monitored for 2–3 months, and the weekly baseline iEEG recordings showed long‐term stability. The low‐dose group (1 μL 4‐AP, 40 mm, n = 5) exhibited local electrographic seizures without spread to the contralateral cerebral cortex or brainstem. The high‐dose group (5 μL 4‐AP, 40 mm, n = 3) had several hippocampal electrographic seizures, which spread contralaterally and triggered brainstem discharges within 40 min, and were associated with violent motor seizures followed by dyspnea and respiratory arrest, with cortical and hippocampal iEEG flattening. The group that received high‐dose 4‐AP without brainstem implantation (n = 5) had similar seizure‐related respiratory difficulties. Finally, five rats that received high‐dose 4‐AP without EEG recording also developed violent motor seizures with postictal respiratory arrest. Following visualized respiratory arrest in groups III, IV, and V, manual respiratory resuscitation was successful in five of 13 animals. Significance: These studies show that hippocampal seizure activity can spread or trigger brainstem epileptiform discharges that may cause mortality, possibly mediated by respiratory network dysfunction.